2021
DOI: 10.1017/s0003055421000022
|View full text |Cite
|
Sign up to set email alerts
|

Gone For Good: Deindustrialization, White Voter Backlash, and US Presidential Voting

Abstract: Globalization and automation have contributed to deindustrialization and the loss of millions of manufacturing jobs, yielding important electoral implications across advanced democracies. Coupling insights from economic voting and social identity theory, we consider how different groups in society may construe manufacturing job losses in contrasting ways. We argue that deindustrialization threatens dominant group status, leading some white voters in affected localities to favor candidates they believe will add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 83 publications
3
80
0
Order By: Relevance
“…In a recent paper, Baccini and Weymouth ( 2021 ) found that white voters were more likely to support Trump in light of local manufacturing layoffs, with their argument being this group perceives such job losses as a threat to upward mobility. Replication of their method using ANES data suggests that their measure of job displacement is far more correlated with our macro insecurity index than with our micro metric.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent paper, Baccini and Weymouth ( 2021 ) found that white voters were more likely to support Trump in light of local manufacturing layoffs, with their argument being this group perceives such job losses as a threat to upward mobility. Replication of their method using ANES data suggests that their measure of job displacement is far more correlated with our macro insecurity index than with our micro metric.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies show that support for Trump among non-college educated whites was driven more by status threat, racism and sexism than by economic conditions (Mutz, 2018; Schaffner et al, 2018). Of course, deindustrialization can exacerbate status threat, so the relationship is complex (Baccini and Weymouth, 2021). However, even if economic conditions are important underlying factors, the response to those conditions is heavily mediated by ideology, and hardly constitutes a straightforwardly rational reaction.…”
Section: The Trump Eramentioning
confidence: 99%
“…For example, Baccini and Weymouth (2021) show that localized manufacture layoffs increase support for the Republican party in the US only among white voters.…”
Section: Economic Shocks and Political Behaviormentioning
confidence: 99%
“…However, politicians can combine anti-establishment and populist rhetoric with many different policy positions and dimensions (Mudde and Kaltwasser, 2018). I argue that economic shocks interact with local context and individual predispositions to shape the appeal of mainstream and challenger parties (Zaller and Feldman, 1992;Baccini and Weymouth, 2021). More specifically, I focus on formal and informal organizations' role in supporting citizens during times of economic hardship (security schemes).…”
Section: Argument and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation